1999
DOI: 10.3109/13550289909015815
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of PrPSc- and HIV-1 gp120 induced neuronal cell death by sulfated colominic acid

Abstract: The scrapie prion protein (PrP Sc ) has been shown to induce apoptosis of rat cortical neurons in vitro. Here we demonstrate that the toxic effect displayed by PrP Sc can be blocked by sulfated colominic acid (polymer of N-acetylneuraminic acid). This compound acts neuroprotectively at a concentration of 50.3 mg/ml when preincubated with the neurons or PrP Sc . Rat cortical cells also undergo apoptosis after incubation with the HIV-1 coat protein gp120 in vitro. This effect was abolished also by sulfated colom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…O-sulfated CA (SCA), prepared by the chemical sulfation of CA (Mulligan et al, 1998), has several biological activities, including antiviral activities (Young et al, 1996;Ushijima et al, 1999;Konishi et al, 2000), inhibition of the cytotoxic action of bee and snake venom (Oda et al, 1999), inhibition of P-selectin-dependent macrophage infiltration in the glomeruli in experimental crescentic glomerulonephritis in rats (Ogawa et al, 2002), and inhibition of the fertilization of mouse gametes (Kawai et al, 2000). Recently, we have shown that both CA and SCA inhibit the proliferation of cultured vascular smooth muscle cells without nonspecific cell damage .…”
Section: Introductionmentioning
confidence: 99%
“…O-sulfated CA (SCA), prepared by the chemical sulfation of CA (Mulligan et al, 1998), has several biological activities, including antiviral activities (Young et al, 1996;Ushijima et al, 1999;Konishi et al, 2000), inhibition of the cytotoxic action of bee and snake venom (Oda et al, 1999), inhibition of P-selectin-dependent macrophage infiltration in the glomeruli in experimental crescentic glomerulonephritis in rats (Ogawa et al, 2002), and inhibition of the fertilization of mouse gametes (Kawai et al, 2000). Recently, we have shown that both CA and SCA inhibit the proliferation of cultured vascular smooth muscle cells without nonspecific cell damage .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that sulfated colominic acid (SCA, structure is shown in supplemental Fig. 1S) exhibits anti-HIV activity [12], and suppresses scrapie prion protein (PrP Sc ) and HIV-1 gp-120-induced neuronal cell death [13]. Since recent accumulating evidences suggest that CXCR4 and CD26 play critical roles in HIV entry as co-receptors [14,15], it is possible that SCA modulates CXCR4 and/or CD26.…”
Section: Introductionmentioning
confidence: 99%
“…1B), originally isolated from Escherichia coli K1. 21) Although little is known about the biological activity of CA, O-sulfated CA (SCA), prepared by chemical sulfation of the CA chain, 22) exhibits several biological activities, including antiviral activities, [23][24][25] inhibition of the cytotoxic action of bee and snake venom, 26) inhibition of Pselectin-dependent macrophage infiltration in the glomeruli in experimental rats with crescentic glomerulonephritis, 27) and inhibition of the fertilization of mouse gametes. 28) However, the effects of CA and SCA on the vascular cell functions as well as the blood coagulation-fibrinolytic system have not been investigated.…”
Section: Introductionmentioning
confidence: 99%